PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE MAKE A MATCH TERHADAP HASIL BELAJAR KEWIRAUSAHAAN SISWA KELAS X PEMASARAN - Ningrum Ningrum; Lilian Mega Puri (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
Based on the results of preliminary observations of entrepreneurial values at SMK Muhammadiyah 1 Seputih Banyak class X students still have many learning outcomes that have not reached the minimum completeness criteria (KKM). The learning outcomes of students who have not completed with the number of students are 17 percentages 56.07%, who achieve learning completeness and are categorized as complete with the number of students 13 percentages 43.33%, while the minimum completeness value (KKM) class X marketing SMK Muhammadiyah 1 Seputih Banyak In entrepreneurship lessons is 75. Alternatives to improve student learning outcomes are used the cooperative learning model type make a match, in connection with this problem the formulation of the problem is: "is there an effect of using the make a match type cooperative learning model on the learning outcomes of students in class X marketing even semester of SMK Muhammadiyah 1 Seputih Banyak for 2019/2020 academic year ". The results of the analysis of the calculation of t count and t table above means that it is known that t count> t table. It can be seen in list G, on the significant list 5%, namely 4.69> 1.70 and at the 1% significant level, namely 4.69> 2.47, thus the hypothesis reads: there is a positive effect using the cooperative learning model make a match Regarding entrepreneurial learning outcomes in X grade marketing students of even semester SMK Muhammadiyah 1 Seputih Banyak, the hypothesis is accepted, students who are said to be complete with KKM (75) after treatment are 21 students or 72.41% and students who are declared incomplete as many as 8 students or 27.59%. Therefore, to improve student learning outcomes, teachers should apply the cooperative learning model make a match type in organized learning.Keyword : Cooperative Learning, Tipe Make A Match, Learning Outcomes